Evaluación del sistema de competencias de especialización de docentes y estudiantes de la carrera de inglés de la escuela de ciencias de la educación de la universidad técnica de Machala, período lectivo 2012-2013 y propuesta de capacitación y aplicación de las Tics en círculos de estudios para potenciar destrezas, habilidades y competencias. - Ordoñez León, Lorena Alexandra (2015)
The research entitled Evaluation of the powers of specialization of teachers and students English carrea schools of science education at the Technical University of Machala , school year 2012-2013 and proposed training and application of ICTs in circles studies to enhance skills , skills and competencies was conducted at the Technical University of Machala , in the Academic Unit of Social Sciences, English race . It was conducted under the qualitative approach where instruments such as interview and observation to authorities, teachers and students in order to determine how you can optimize the use of ICT for teaching practice improve the learning process were applied.